1976
DOI: 10.1070/qe1976v006n05abeh011360
|View full text |Cite
|
Sign up to set email alerts
|

Observation of optical inhomogeneities in the active medium of an F2+D2(H2)+CO2chemical laser

Abstract: The diffusivity of Mn in CdTe, D(Mn), has been measured between 500 and 800 "C under saturated Cd and Te condaions. The variation of D(Mn) with Cd partial pressure was measured at 600 'C. Between 500 and 800 "Cfor saturated Te, and between 600 and 800 "C for saturated Cd D(Mn) = (1.12:9,12) x 1O3exp(-(2.76i0.18)eV/kT) cm2 s-', These results are consistent with those at 600 "C which show D(Mn) to increase with decreasing Cd partial pressure. It is argued that lhe observed features of D(Mn) can be best accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Among theses factors there are diffraction phenomena occurred on an optical aperture and optical uniformity ofan active medium. Investigations carried out by employees ofour Institute showed that a characteristic feature of a chemical laser is a very high optical uniformity superior to that of other kinds of lasers [21,22].…”
Section: Dependence Of Average Specific Output Energy Of Initiatedmentioning
confidence: 99%
“…Among theses factors there are diffraction phenomena occurred on an optical aperture and optical uniformity ofan active medium. Investigations carried out by employees ofour Institute showed that a characteristic feature of a chemical laser is a very high optical uniformity superior to that of other kinds of lasers [21,22].…”
Section: Dependence Of Average Specific Output Energy Of Initiatedmentioning
confidence: 99%